X-Linked Mental Retardation: A Case Report - Akın, Haluk; Yüce, Hüseyin; Tekedereli, İbrahim (Fırat University, 2007)
The patient is 14 years old male patient with mental retardation, gynecomastia and obesity. Borjeson-Forssman- Lehmann syndrome presumed after the clinical and laboratory studies. Given the ease of expression of X-linked disorders in hemizygous males, the X-chromosome has become an obvious focus for beginning to map and identify genes for syndromal and nonspecific mental retardation. ©2007, Firat University, Medical Faculty

Mental retardasyon, jinekomasti ve obesitesi olan 14 yaşındaki erkek hastanın yapılan tetkik ve muayenesi sonucu Borjeson-Forssman- Lehmann sendromu ön tanısı kondu. X'e bağlı hastalıkların, erkeklerin hemizigot olması nedeniyle X kromozomu sendromik veya non sendromik mental retardasyon genlerinin belirlenmesi ve haritalanması için açık bir lokus haline gelmiştir. ©2007, Fırat Üniversitesi, Tıp Fakültesi
X'e Bağlı Mental Retardasyon: Bir Olgu